Selection and Characterization of a Novel DNA Aptamer, Apt-07S Specific to Hepatocellular Carcinoma Cells - Yu XX; Ge KL; Liu N; Zhang JY; Xue ML; Ge YL (Dove Medical Press, 2020)
Xiao-Xia Yu,1,* Ke-Li Ge,2,* Ning Liu,3 Jin-Yu Zhang,1 Mei-Lan Xue,1 Yin-Lin Ge1 1Department of Biochemistry and Molecular Biology, Basic Medical College, Qingdao University, Qingdao, Shandong Province 266071, People’s Republic of China; 2Integrative Medicine Research Center, Medical College, Qingdao University, Qingdao 266021, Shandong Province, People’s Republic of China; 3Department of Dermatology, Qingdao Municipal Hospital, Qingdao 266071, Shandong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yin-Lin GeDepartment of Biochemistry and Molecular Biology, Basic Medical College, Qingdao University, 308 Ningxia Road, Qingdao 266071, People’s Republic of ChinaEmail geyinlin@126.comBackground: The efficacy of traditional therapeutic methods for liver cancer is unsatisfying because of the poor targeting, and inefficient drug delivery system. A recent study has proven that aptamers, developed through cell-SELEX, could specifically recognize cancer cells and show great potential in the development of a delivery system for anticancer drugs.Purpose: To develop a hepatocellular carcinoma specific aptamer using two kinds of hepatocellular carcinoma cell lines, HepG2 and SMMC-7721, as double targets and a normal hepatocyte, L02, as a negative control cell.Methods: Hepatocellular carcinoma specific aptamer was developed via cell-SELEX. The enrichment of the library was monitored by flow cytometric analysis. The specificity, affinity, and distribution of the candidate aptamer were explored. Further study was carried to assess its potential in drug delivery.Results: The library was enriched after 14 rounds of screening. Candidate aptamer Apt-07S can recognize four kinds of hepatocellular carcinoma cells and show little cell-binding ability to normal cells and four cell lines of different cancer types, revealing a high specificity of Apt-07S. Confocal imaging showed that Apt-07S distributed both on the surface and in the cytoplasm of the two target cells. Moreover, an anti-sense nucleotide to gene Plk1 (ASO-Plk1) was connected at the 3ʹ end of Apt-07S to form an integrated molecule (Apt-07S-ASO-Plk1); the functional analysis indicated that the structure of Apt-07S may help ASO-Plk1 enter the cancer cells.Conclusion: The study indicates that Apt-07S can specifically target HCC and may have potential in the delivery of anticancer drugs.Keywords: aptamer, cell-SELEX, hepatocellular carcinoma, double target